Do mergers of large local governments reduce expenditures? Evidence from Germany using the synthetic control method - Felix Roesel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
States merge small and medium sized municipalities to achieve economies of scale.Little is known to which extent mergers of large local governments reduce expenditures.I use the synthetic control method to identify the effect of mergers of county-sizedadministrations in Germany (districts) on public expenditures. In 2008, the Germanstate of Saxony reduced the number of districts from 22 to 10. Average district populationincreased substantially from 113,000 to 290,000 inhabitants. I construct a “SyntheticSaxony” serving as counterfactual to real Saxony from districts of ten other Germanstates that did not merge districts for years. The results do neither show that districtmergers reduce total expenditures per capita, nor expenditures in main expenditurecategories such as social care, education or administration. There seems to be no scaleeffects in jurisdictions of more than 100,000 inhabitants.
Keywords: I28; I21; H75; 330; Bologna Reform; Bachelor introduction; student outcomes; instrumental variables